2019
DOI: 10.1002/col.22352
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of color design for military camouflage in CIELAB color space

Abstract: The assessment of military camouflage is a key consideration in the modern military field. Traditionally, the assessment relies on traditional human visual detection tests because a large scale multi‐level and multi‐factor experiments are time‐ and resource‐consuming. One aspect of camouflage assessment, to which this current study pertains, entails improving upon or “enhancing” an existing or “selected” design. The current study presents a new and practical approach for enhancing the selected military camoufl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The hit rate was defined as the percentage of trials on which the camouflaged target was correctly identified (indicated by clicking on it with the computer mouse), and the detection time was the time between the participant clicking the start button to begin the trial and subsequently clicking on the target (or quitting the trial). The task difficulty was rated on a seven-point rating scale at the end of each trial, ranging from 1 (easiest) to 7 (most difficult) [ 20 , 25 ]. Before the experiment, the experimental procedure was explained to all participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hit rate was defined as the percentage of trials on which the camouflaged target was correctly identified (indicated by clicking on it with the computer mouse), and the detection time was the time between the participant clicking the start button to begin the trial and subsequently clicking on the target (or quitting the trial). The task difficulty was rated on a seven-point rating scale at the end of each trial, ranging from 1 (easiest) to 7 (most difficult) [ 20 , 25 ]. Before the experiment, the experimental procedure was explained to all participants.…”
Section: Methodsmentioning
confidence: 99%
“…CMC (l:c) and CIEDE2000 have been compared, and the camouflage similarity index (CSI) can be used to measure pixel-to-pixel color differences between a camouflaged object and its background using the CIELAB color system [ 19 ]. CSI performs well when used to discriminate an object from a large uniform background [ 20 ]. To process complex images, Spatial-CIELAB (S-CIELAB) [ 21 ] was developed from CIELAB space and takes into account sensitivity to color patterns; it may be superior for analyzing the similarity between a target object and background in assessments of camouflage effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the resulting figure of the PSO is presented in Figure 4 and the overall L 0 *, a 0 *, and b 0 * values were 56.0579, −3.3293, and 10.4340, respectively. 4 | THE SHIFT OF %L*, % a*, AN D % b* Similar to our previous study, 22 one existing military camouflage was selected. Similar existing camouflage was selected since the CSI values of the original, newly proposed camouflage based on RSM, 22 22 We applied our previous algorithm 22 to derive a shift combination of %L*, %a*, and %b from the original camouflage, which results in L 00 *, a 00 *, and b 00 *, which is close to the PSO result.…”
Section: Empirical Parameter Using Psomentioning
confidence: 99%
“…We also present the result of our previous study, which utilized the RSM approach. 22 Based on Table 6, the PSO approach derives a lower CSI value compared to RSM. Even though these two methods were not directly compared, it appears that PSO approach performs better the RSM because it derives a lower CSI value than the RSM.…”
Section: Empirical Parameter Using Psomentioning
confidence: 99%
“…7,8 Recently, new and practical approaches have been developed to enhance military camouflage in the visible area, with relatively few human subject tests, by using response surface methodology (RSM) of %L*, %a*, and %b* in CIELAB color space and investigating the variations of these parameters with regard to the camouflage similarity index (CSI) and reaction time (RT). 9,10 Another advanced camouflage technology in the visible area is the use of chameleon fabrics. In this way, thermochromic colorants were utilized to improve the chameleon effect in the fabrics on application of heat from external sources, such as hot air oven or electrical power.…”
mentioning
confidence: 99%